Analysis of the Use of Financial Resources of Educational Institutions in Uzbekistan - Salokhiddinov Jaloliddin Ulugbek ugli (Scientific Trends, 2024)
In this article , we studied the sources of financing educational institutions and discussed the ways and perspectives of their effective use. We also enriched the article with theoretical, legal and foreign experience information on the topic. Today, it is no secret that the world's prestigious higher education institutions are considered to be the major hotbeds of science. Currently, new higher educational institutions and branches of the world's leading universities are being established. From this point of view, the financial situation in private higher education institutions was analyzed and scientific proposals and practical recommendations were presented on the basis of ways to ensure the stability of sources of income of educational institutions.
Keywords: Educational institutions, public-private partnership, non-governmental educational organizations, contract, income, expenses, republican budget, estimate, state units, income bases, taxes, financial analysis.